CYP4B1 inhibits lung adenocarcinoma progression via PI3K/AKT/mTOR pathway: mechanistic insights and development of a CYP4B1-related prognostic signature - Li, Guoyin; Kang, Jing; Li, Xiaoyan; Zhao, Liping; Chen, Yuhang; Gong, Chenlu; Liu, Zhiqiang; Zhang, Bi (Frontiers in Oncology, 2026)
BackgroundLung adenocarcinoma (LUAD) has a poor 5-year survival rate due to delayed diagnosis and drug resistance. Cytochrome P450 4B1 (CYP4B1), a lung-predominant enzyme, is linked to cancer susceptibility, but its role and regulation in LUAD remain unclear.MethodsMulti-omics analyses of public datasets (TCGA_LUAD, GSE series) and clinical specimens assessed CYP4B1 expression. Functional experiments (cell lines, xenografts) explored its effects. Mechanistic studies (Western blot, ChIP) and transcriptional regulation assays (luciferase reporters) were performed. A CYP4B1-related risk score (CRRS) and nomogram were developed via LASSO-Cox regression and validated.ResultsCYP4B1 is significantly downregulated in LUAD, correlating with poor patient survival (AUC > 0.78 for diagnostic discrimination between LUAD and normal tissues). Functionally, CYP4B1 inhibits LUAD cell proliferation in vitro and in vivo, which is associated with the suppression of the PI3K/AKT/mTOR signaling pathway. We identified a transcriptional regulatory mechanism in which transcription factor nuclear factor I A (NFIA) acts as a key upstream regulator of CYP4B1, activating its transcription via direct binding to the CYP4B1 promoter. The CRRS, constructed based on 7 CYP4B1-related core genes, effectively stratified patients into high/low-risk groups with divergent survival outcomes in both training and validation cohorts, and correlated with drug sensitivity. A nomogram integrating CRRS and clinical variables achieved reliable prediction of 1-/3-/5-year survival (AUC > 0.72).ConclusionCYP4B1 functions as a tumor suppressor in LUAD, regulated by NFIA and exerting its effects through PI3K/AKT/mTOR pathway inhibition. The CRRS and nomogram provide potential tools for prognosis assessment and offer guidance for precision therapy in LUAD, pending further translational validation.